1998
DOI: 10.1074/jbc.273.18.11158
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of Glycine Antagonist Sites ofN-Methyl-d-aspartate Receptor Subtypes

Abstract: The binding site for the co-agonist glycine on N-methyl-D-aspartate (NMDA) receptors has been mapped to the NR1 subunit whereas binding of the principal agonist glutamate is mediated by the NR2 subunits. block, slow activation and inactivation kinetics, and the requirement for glycine as a co-agonist in channel gating (1-6). They play a crucial role in brain development, synaptic plasticity and the pathophysiology of major neurological disorders (7-11). NMDA receptors are assembled from the NR1 subunit in comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
2

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(18 citation statements)
references
References 59 publications
1
15
0
2
Order By: Relevance
“…Molecular models of both the pore forming region and agonist binding domain of homomeric NMDA-R2C and heteromeric NMDA-R1/R2C channels have been produced. The models provide an explanation for the lack of functional ion channel activity for homomeric NMDA-R2 receptors and provide insights into the differential interactions of these two subunits with glycine and glutamate [18][19][20]. This study extends our earlier work [21], performed before the crystal structures of the agonist binding domain of GluR2 [22] and the KcsA K + channel [23] were available.…”
supporting
confidence: 71%
See 1 more Smart Citation
“…Molecular models of both the pore forming region and agonist binding domain of homomeric NMDA-R2C and heteromeric NMDA-R1/R2C channels have been produced. The models provide an explanation for the lack of functional ion channel activity for homomeric NMDA-R2 receptors and provide insights into the differential interactions of these two subunits with glycine and glutamate [18][19][20]. This study extends our earlier work [21], performed before the crystal structures of the agonist binding domain of GluR2 [22] and the KcsA K + channel [23] were available.…”
supporting
confidence: 71%
“…lower than that expected based on percentage amino acid sequence identity [46]. NMDA-R1 subunits are thought to bind glycine whereas the NMDA-R2 subfamily are thought to bind glutamate [18][19][20]. It has been suggested [20] that this difference in binding may arise from the presence of bulky aromatic sidechains in the α-amino binding region of NMDA-R1 subunits.…”
Section: Agonist-binding Domainmentioning
confidence: 79%
“…For example, MDL105,519 does not distinguish between all four NR1‐1a/NR2 forms but in functional studies, L689,560 has a 5 fold selectivity for NR1‐1a/NR2A compared to NR1‐1a/NR2B receptors and notably, the antagonist response curve for NR1‐1a/NR2A deviated from sigmoidal behaviour ( Hess et al ., 1996 ); DKA has an approximate 2 fold lower affinity for NR1‐NR2B, NR1/NR2D compared to NR1/NR2A and NR1/NR2C ( Laurie & Seeburg, 1994 ). More recently, it was shown that [ 3 H]‐CGP 61594, a glycine site antagonist which is also a photoaffinity ligand, preferentially labelled NR2B‐subunit containing NMDA receptors although the incorporated radioactivity was associated with only the M r ∼120 000 NR1 subunit ( Honer et al ., 1998 ). A low affinity reversible binding site for [ 3 H]‐CGP 61594 was found in rat cerebellar membranes.…”
Section: Discussionmentioning
confidence: 99%
“…A low affinity reversible binding site for [ 3 H]‐CGP 61594 was found in rat cerebellar membranes. It was attributed to binding to NR1/NR2A, NR1/NR2C or both subtypes of receptor since these are the subunits expressed in adult cerebellum ( Honer et al ., 1998 ).…”
Section: Discussionmentioning
confidence: 99%
“…Potencies for the agonists glycine, D-serine, D-alanine, and 1-amino-carboxycyclobutane are significantly lower at NRlINR2A receptors than receptors composed of NRlINR2B, NR1!NR2C and NRlINR2D (ranked in order of increasing potency; PRIESTLEY et al 1995, LAURIE andSEEBURG 1994;KUTSUWADA et al 1992;BULLER et al 1995;MATSUI et al 1995;HESS et al 1996). Recently a glycine-site antagonist WH]CGP 61594) has been shown to display a high affinity selectively for NR2B-containing receptors (HONER et al 1998). …”
Section: Radioligand Binding and Fnnctional Characteristics Of The Glmentioning
confidence: 96%